The Relationship between the Level of Knowledge About HIV/AIDS and the Attitudes of Adolescents Aged 13-21 Years on Premarital Sexual Behavior In Naman Teran Village in 2023 - Hanry Anta Lesmana; Jenny Meliala; Ernawati Br Barus (Sean Institute, 2023)
Premarital sexual behavior is any sexual activity or activity that is motivated by sexual desire carried out before marriage, both religiously and legally. The World Health Organization (2018), states that around 21 million adolescent girls aged 15–19 years in developing countries experience pregnancy every year and almost half of these pregnancies (49%) are unwanted pregnancies. One of the reasons for this pregnancy is sex before marriage. Reports on the development of HIV AIDS in Indonesia from October to December 2022 reported the number of people infected with HIV as many as 14,640 people. The number of people with AIDS was reported as many as 4,725 people. The highest presentation of HIV infection was reported in the age group 25-49 years (69.2%) followed by the age group 20-24 years (16.7%) and the age group over 50 years (7.6%). The highest presentation of AIDS was in the age group 30-39 years (35.2%) followed by the age group 20-29 years (29.5%) and the age group 40-49 years. Based on data from the 2022 District/City Health Profile, there were 1,352 additional new HIV cases in 2022 and 392 AIDS deaths. With this increase, by 2022 the total number of HIV cases will be 6,210 cases and AIDS will be 5,625. The development of HIV/AIDS cases in North Sumatra among school children or students is 2,034 people. Based on 2021 data, the three regencies/cities with new HIV/AIDS sufferers in succession are Medan City, namely 617 cases or around 35.38%, Deli Serdang Regency with 189 cases (10.84%) and Karo Regency with 178 cases (10 .20%) .